أثر تكنولوجيا المعلومات والاتصال على النمو الاقتصادي (دراسة قياسية للجزائر خلال الفترة 1990-2020) - خوالدي, سليمة; دردور, اسماء (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى قياس أثر تكنولوجيا المعلومات والاتصال على النمو الاقتصادي في الجزائر خلال الفترة 1990-2020 حيث استخدمت مؤشرات تكنولوجيا المعلومات والاتصال (عدد مشتركي الهاتف النقال وعدد مشتركي الهاتف الثابت) كمتغيرات مستقلة واستخدام الناتج المحلي الإجمالي كمتغير تابع يمثل النمو الاقتصادي. وقد توصل البحث إلى مجموعة من النتائج أهمها وجود علاقة توازنية طويلة الأجل فضلا عن العلاقة قصيرة الأجل (نموذج تصحيح الخطأ) بين متغيرات تكنولوجيا المعلومات والاتصال والناتج المحلي الإجمالي، مع وجود علاقة ايجابية بين عدد مشتركي الهاتف النقال والنمو الاقتصادي. The study aims to determine the impact of information and communication technology on GDP in Algeria during the period (1990-2020) use ARDL model. Were used an independent variables representing information and communication technology (Number of mobile subscribers, Number of fixed phone subscribers) and the dependent variable represented in the GDP. The study reached a number of results the most important of which is the existence of a long term equilibrium relationship as well as the short term relationship(error correction model) between the variables of information and communication technology and economic growth, a positive relationship between the Number of mobile subscribers and GDP
The effect of information and communication technology on economic growth (econometric study in algeria during 1990-2020)
مقال
Keywords: تكنؤلؤجيا المعلؤمات ؤالاتصال ; النمؤ الاقتصادي ; الجزائر ; نمؤذج ARDL